Relationship of Peripapillary Retinal Perfusion with Peripapillary Retinal Nerve Fiber Layer Thickness in Diabetes Mellitus Patients without Diabetic Retinopathy - Dwijayanti, Sindi; Irfani, Irawati; Sirait, Susanti Natalya; Gustianty, Elsa; Iskandar, Erwin; Kartiwa, R. Angga (Indonesian Vitreoretinal Society, 2021)
Introduction: Impaired blood flow is an early sign of retinal dysfunction in diabetes. Impaired blood flow of the radial peripapillary capillaries can affect the Retinal Nerve Fiber Layer (RNFL) or ganglion cell function. Methods: This was an analytic cross-sectional study in February-April 2019 at Bandung. The subjects of this study were 41 people (79 eyes) divided into two groups, group A (healthy subjects) 19 people (37 eyes) and group B (DM type 2 without diabetic retinopathy) 22 people (42 eyes). Peripapillary retinal perfusion was assesed using OCT Angiography and RNFL thickness was assesed using OCT. Pearson or Spearman correlation statistics test was used to analyze the result. P value ≤0.05 was consiedered significant. Results: There was a decrease in peripapillary retinal perfusion density in the inferior quadrant (P = 0.003) and flux index throughout the peripapillary retinal quadrant (P = 0.0001) but an increase in RNFL thickness in the peripapillary temporal quadrant (P = 0.012) compared to control grup. Positive correlation was found between peripapillary retinal perfusion density and RNFL thickness globally (r = 0.480, P = 0.001), superior quadrant (r = 0.436, P = 0.004), and inferior quadrant (r = 0.608, P = 0.000). A positive correlation was also found between the peripapillary flux and RNFL thickness globally (r = 0.517, P = 0.000), superior quadrant (r = 0.630, P = 0.000), and inferior quadrant (r = 0.519, P = 0.000). Conclusions: There was a relationship between peripapillary retinal perfusion and RNFL thickness in DM patients without diabetic retinopathy. Keywords: Peripapillary perfusion, RNFL thickness, Diabetes.